Implementation of World Health Organization behaviorally anchored rating scale and checklist utilization: promising results for LMICs - Khalid, Syed Yousaf; Sibghatullah, Qazi Muhammad; Abdullah, Muhammad Haroon; Farooq, Omer; Ashraf, Sandal; Ahmed, Adeel; Arshad, Ashhar; Nadeem, Abdullah; Mumtaz, Hassan; Saqib, Muhammad (Frontiers in Medicine, 2023)
Abstract: Background: Operating teams can decrease the likelihood of patient risk by using the WHO Surgical Safety Checklist. In order to ascertain the impact of demographic factors on behaviorally anchored ratings and investigate operating room (OR) staff attitudes toward checklist administration, we set out to better understand how OR personnel use the checklist in a tertiary care hospital in Pakistan. Materials and Methods: A monocentric sequential mixed-methods study employing a quantitative approach of using WHOBARS (World Health Organization Behaviorally Anchored Rating Scale) assessments of surgical cases by OR personnel and two independent observers who were certified surgeons that had extensive experience in rating of the WHOBARS scale for more than 1 year, followed by a qualitative approach of staff interviews was carried out in a tertiary care setting. In June and July of 2022, over the period of eight weeks, an intervention (training delivery) was implemented and evaluated. The information, skills, and behavior adjustments required to apply the checklist were taught in the course using lectures, videos, small group breakouts, participant feedback, and simulations. Results: After the introduction of WHOBARS, 50.81% of respondents reported always using the checklist, with another 30.81% using it in part. Participant’s years in practice, hospital size, or surgical volume did not predict checklist use. Checklist use was associated with always counting instruments (51.08%), patient identity (67.83%), difficult intubation risk (39.72%), risk of blood loss (51.08%), prophylactic antibiotic administration (52.43%), and use of pulse oximeter (46.75%). Interviewees felt the Checklist could promote teamwork and a safety culture, particularly enabling speaking up. Senior staff were of key importance in setting the appropriate tone. Conclusion: The use of a multi-disciplinary course for checklist implementation resulted in 50.81% of participants always using the checklist; and an increase in counting surgical instruments. Successful checklist implementation was not predicted by participant length of medical service, hospital size or surgical volume. If reproducible in other countries, widespread implementation in LMICs becomes a realistic possibility.